Radio/X-ray correlations and variability in the X-ray binary LS I +61°303. Issue 3 (17th November 2020) - Sharma, R; Massi, M; Chernyakova, M; Malyshev, D; Perrott, Y C; Kraus, A; Dzib, S A; Jaron, F; Cantwell, T M
ABSTRACT: The high-mass X-ray binary LS I +61°303 exhibits variability in its radio and X-ray emissions, ranging from minute to hour time-scales. At such short time-scales, not much is known about the possible correlations between these two emissions from this source, which might offer hints to their origin. Here, we study the relationship between these emissions using simultaneous X-ray and radio monitoring. We present new radio observations using the Arcminute Microkelvin Imager Large Array telescope at two frequency bands, 13–15.5 and 15.5–18 GHz. We also describe new X-ray observations performed using the XMM–Newton telescope. These X-ray and radio observations overlapped for five hours. We find for the first time that the radio and X-ray emission are correlated up to 81 per cent with their few per cent variability correlated up to 40 per cent . We discuss possible physical scenarios that produces the observed correlations and variability in the radio and X-ray emission of LS I +61°303.